Making Video Animations with Daily Life and Family Themes for Hören A1 - Cinta Caroline Hasian Pardede; Ahmad Bengar Harahap (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The purpose of this study is to create an animated video with the topic "daily life and family" using the wondershare filmora application. This study used a qualitative descriptive method. The process of making an animated video with the theme "Daily Life and Family" is to explain the stages of Richey and Klein's theory. This includes: (1) the planning phase, (2) the creation phase, (3) the evaluation phase. The data for this study are available in the form of images, materials (plots and video scripts) and exercises on the topic of "daily life and family". The data source for this study is the A1 network with the topic "Daily life and family" in chapter 5, pages 54-63. This research was conducted at the German Language Institute, Faculty of Languages ​​and Arts, State University of Medan. The evaluation results showed that the results of the animated video were very good. So it can be used as a learning medium for German language lessons.